Il respiro corto dello Spirito nelle mega-chiese, ai tempi della pandemia - Pace, Enzo (Comparative Cultural Studies: European and Latin American Perspectives, 2021)
What effect has the pandemic on Mega-churches? The forced closure or drastic reduction of those present admitted to religious services has in fact called into question both the regime of truth that many of these churches follow, from the theological and spiritual point of view, and the drama-liturgy of hand-to-hand combat between the transmormative force of the Spirit and the prince of all evils, Satan. In this way, Mega-churches moved from the mass event experienced in large auditoriums to an online service, on a domestic scale, for many anonymous and distant faithful, to which a consoling message can be conveyed in a phase of inconvenience and suffering in their daily life. The epidemic has stolen the scene from the great performers of the Mega-churches and from those who, enthusiastic, took their seats in the stalls or moved freely possessed by spirits waiting to be freed, actively participating in the deliverance’s rite. These faithful, probably, now watching from a distance at home, in front of their computer screen, another scene, less involving and, above all, without the parrhesia of the regime of truth, which materialized in the ritual space. The epidemic represents a double contingency for the Mega-churches: on the one hand, it weakens the theological vision of a God who can do everything and of the Spirit who blows triumphantly and defeats all evil, on the other, it dematerializes the presence of the enemy who becomes invisible and intrusive, no longer physically dominable, from which no charismatic leader is more able to delivere the faithful.